The spirografic oxygen deficit: Its role in cardiopulmonary exercise testing - Sperlich, B.; Schiffer, T.; Hoffmann, U.; Strueder, H. K.; Hollmann, W. (International Journal of Sports Medicine, 2013)
The increase in oxygen uptake > 100 ml/min during steady state exercise when elevating the inspired fractional air content (FinO2) from 0.21-1.00 defines the "spirografic oxygen deficit" (SOD). The purpose of this study was 2-fold: 1) determine the SOD at different exercise intensities in healthy participants and 2) investigate if a correlation exists among key variables of cardiopulmonary exercise testing. 12 men (24±2 yrs; 183±4 cm; 83.5±5.3 kg) performed cycle tests to determine maximal power output (Pmax), the power output at the first (PVT1) and the second ventilatory threshold (PVT2), at 4 mmol/l blood lactate (P4) and lactate threshold (PLT). When cycling at 30, 40, 50, 60, 70 and 80% Pmax, the FinO2 was increased from 0.21-1.00 after 5 min to assess the power output at the SOD and at which blood lactate increased > 1 mmol/L (PLLAC). The SOD occurred at 70% Pmax accompanied by increased blood lactate concentration (p<0.01). The PSOD correlated with PLACC (p=0.05; r=0.61), but not with PVT1, PVT2, P4, or PLT (best p=0.29; highest r=0.39). In conclusion, the SOD may represent a non-invasive tool for evaluating submaximal endurance performance, especially when evaluating the peripheral contribution to performance.